2002
DOI: 10.1291/hypres.25.689
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological Evidence of the Association between Dietary Protein Intake and Blood Pressure: A Meta-Analysis of Published Data.

Abstract: The purpose of this study was to address the association between dietary protein intake and blood pressure

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
34
0
1

Year Published

2004
2004
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(37 citation statements)
references
References 31 publications
(43 reference statements)
0
34
0
1
Order By: Relevance
“…13 The Intersalt Study, a large cross-sectional international study with 10 020 men and women aged 20-59 years from 54 population-based samples in 32 countries worldwide, also demonstrated that total dietary protein intake had an inverse relationship with BP. 23 Similarly, Liu et al 22 concluded in a metaanalysis report that the inverse association between dietary protein intake and BP was quite convincing in nine population-based cross-sectional studies. In addition, the inverse relationship between total protein intake and BP was further supported by two large controlled feeding trials.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…13 The Intersalt Study, a large cross-sectional international study with 10 020 men and women aged 20-59 years from 54 population-based samples in 32 countries worldwide, also demonstrated that total dietary protein intake had an inverse relationship with BP. 23 Similarly, Liu et al 22 concluded in a metaanalysis report that the inverse association between dietary protein intake and BP was quite convincing in nine population-based cross-sectional studies. In addition, the inverse relationship between total protein intake and BP was further supported by two large controlled feeding trials.…”
Section: Discussionmentioning
confidence: 94%
“…[20][21][22] Intake of total protein and fibre was reported to have significant additive effects in lowering 24-h and All results are controlled for age, gender, race, treatment, study site, education, income, baseline blood pressure and changes of alcohol intake, physical activity, waist circumference, urinary creatinine, sodium excretion, body weight and dietary intake of calcium, and potassium at 6 or 18 months, respectively. All dietary intake variables are either as per cent of calories (protein and fat intake) or as g per 1000 kcal per day (alcohol, fibre), mg per 1000 kcal per day (calcium and potassium).…”
Section: Discussionmentioning
confidence: 99%
“…It is therefore likely that the higher protein intake in the high-protein diet was responsible for the attenuated rise in blood pressure. Observations from several large epidemiological studies [30,31] and short-term (6-13 week) clinical trials [32,33] have demonstrated that protein intake may be inversely related to blood pressure, although which component of dietary protein might be involved is unclear. The present data also support the hypothesis that a long-term higher protein intake may help to lower blood pressure and CVD risk in people with diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, the HP-LF diet lowered significantly more systolic and diastolic blood pressure compared with the LP-HF diet, independent from weight loss, sodium or fiber content of the diet. Liu et al (2002) in a metaanalysis of nine cross-sectional studies found a significant inverse association between dietary protein and blood pressure in both genders. It has been suggested that potentially protein intake could influence arterial BP through the actions of its constituent amino acids (Ginsberg, 2000;Barre, 2007).…”
Section: Methodsmentioning
confidence: 99%